The travelling prayer mat / Norashikin Saifullah, Norwani Mohd Nawawi and Firdaus Mohd Khalid - Saifullah, Norashikin; Mohd Nawawi, Norwani; Mohd Khalid, Firdaus (Research Innovation Business Unit, 2014)
This research is discussed on the multiple function of a travelling praying mat prototype used by Muslim travellers to pray. Nowadays many praying mats in the market are produced from unsuitable material for travelling. Thus, material, size and usability of praying mat is important for travelling purpose. The material used in the praying mat is waterproof material i.e. PVC and waterproof canvas with this material can help Muslim travellers easily maintain the mat from dirt and water if expose to rain. Every Muslim around the world performs prayers when they hear the adhan (called to prayer). This prayer mat contains a compass to enable the worshipper to find the direction of Makah. the benefit for muslim traveller is they can used the kiblah compass to find the direction of Makah. In addition, the mat is foldable type such as a sling bag, purse, hand bag and bag pack. This allows Muslim travellers to carry it easily anywhere. The mat can be used as a place to store item i.e. prayer cloth, Quran, counting beads and etc. The design on this mat is created using adobe illustration and adobe Photoshop. This prayer mat is printed using digital printing technique. The pattern suggests printing on the material such as fabric of PVC type, waterproof canvas, and any suitable waterproof material. The design of this mat was a combination of geometric arabesque design and Malay kerrawang. The combination of two designs on prayer mat represents the Malaysian identity. At the same time, it also can promote Malaysian products world-wide. Furthermore, this travelling mat comes in a variety of sizes for portability and also with a difference shape of arch. The significance of this product is the Muslim traveller can use this mat to perform the prayer anywhere and also as a sleeping mat and it also can be used as picnic mat. the combination of colour used on prayer mat is tones colour from light to dark colour i.e. earth colour which are brown, royal blue and turquoise blue.